Null models for study Rotifers and Crustaceans Zooplankton species richness in Chilean Patagonian lakes - Patricio de los Ríos Escalante (Acta Limnologica Brasiliensia)
Abstract Aims The Patagonian lakes are characterized by their oligotrophy that is the cause of low species number in their zooplankton assemblage. The aim of the present study is to analyze the crustacean and rotifers species number pattern in Patagonian lakes among a latitudinal gradient (40-51 °S). Results The results revealed that there are direct significant correlations between total species with rotifer species, and chlorophyll concentration with crustacean species number, and an inverse association between latitude with total species. Conclusion The results of co-occurrence species null model revealed presence of regulator factors in one of three simulations, that would be due to the presence of many species repeated in studied sites. Similar patterns were observed in Argentinean Patagonian lakes.